Authority Limits of POLRI and BNN Investigators in Narcotics Law Enforcement - Nababan, Jui Dermawati; Hayati, Mulida; Pramita, Claudia Yuni (Academia Open, 2026)
General Background Narcotics crimes in Indonesia are categorized as extraordinary crimes requiring integrated law enforcement within the criminal justice system. Specific Background The Indonesian National Police and the National Narcotics Agency (BNN) both possess investigative authority in handling narcotics cases, which often leads to overlapping roles in practice. Knowledge Gap The absence of clear operational boundaries and coordination mechanisms between these institutions creates legal uncertainty and potential duplication in narcotics investigations. Aims This study aims to analyze the legal framework governing investigative authority and examine the coordination challenges between the Police and BNN in narcotics crime handling. Results The findings indicate that overlapping authority between institutions contributes to inefficiencies, procedural inconsistencies, and conflicts in law enforcement practices, particularly in investigation stages and case handling. Existing regulations provide formal authority but lack detailed technical guidelines for coordination. Novelty This study highlights the structural and normative gaps in inter-agency coordination by emphasizing the need for integrated operational standards within narcotics investigations. Implications Strengthening regulatory clarity and establishing joint operational guidelines are essential to ensure legal certainty, prevent duplication of authority, and support a more coherent criminal justice process in addressing narcotics crimes in Indonesia. Highlights: Dual institutional mandates generate procedural overlap in case handling. Regulatory provisions lack detailed coordination mechanisms at the operational level. Inter-agency inconsistency contributes to inefficiency in investigation processes. Keywords: Investigative Authority, POLRI, BNN, Narcotics Crimes.